Factors that Influence The Onset of Acne Vulgaris :Retrospective Study - Asrianti, Nur Ilma; Trisniartami Setyaningrum; Yuani Setiawati; Yuri Widia (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Acne vulgaris (AV) is a skin condition that mostly occurs in adolescents, although it can occur at any age. Most occur during adolescence, with a prevalence of around 85%. Acne vulgaris is a multifactorial disease triggered by many factors, namely, genetics, environment, hormonal and emotional stress, food, trauma, cosmetics, and medications. Purpose: This study identifies the precipitating factors of acne vulgaris. Methods: This study was retrospective based on medical record data at the Dermatology and Venereology Outpatient Clinic of Dr. Soetomo General Academic Hospital Surabaya in the period January 2018–December 2019. Results: The number of AV patients within 2 years from January 2018 to December 2019 obtained 517 cases of acne vulgaris patients with complete data. There were female AV patients (80.7%) and male AV patients (19.3%). The most common age of AV patients was 15–24 years old (60.5%), the most common occupation of AV patients was student (59.8%), and patients suffered from AV for >12 months (18.6%). The most precipitating factors for AV are hormonal (69.6%) and cosmetic (50.1%); the most common type of AV is mild AV (64.2%); and the most common AV therapy is the combination of topical tretinoin, benzoyl peroxide (BPO), and topical clindamycin. Conclusion: The results of this study showed that hormonal and cosmetic precipitating factors caused most AV patients in women.